Can Pop Culture Allay Resentment? Japan’s Influence in China Today - Yuqing Wu (Media and Communication, 2021)
In China, despite the traumatic collective memory relating to militaristic Japan during World War II, an increasing number of Chinese young adults have developed an obsession with Japanese culture, due to its export of anime, movies, pop music, and other popular culture. Based on interviews with 40 Chinese and Japanese young adults, this work examines how contemporary pop culture and historical war memories related to Japan influenced Chinese young adults, who had to reconcile their contradictory sentiments toward the Japanese government, people, and culture. The success of Japanese pop culture in China also shows how the allegedly apolitical, virtual sphere of entertainment has helped build Japan’s soft power through shaping a cool image of Japan in Asia and worldwide.